High-resolution 3D unenhanced ECG-gated respiratory-navigated MR angiography of the renal arteries: comparison with contrast-enhanced MR angiography - Mohrs, Oliver K.; Petersen, Steffen E.; Schulze, Thomas; Zieschang, Michael; Küx, Harald; Schmitt, Peter; Bergemann, Sabine; Kauczor, Hans-Ulrich (American journal of roentgenology, 2010)
OBJECTIVE. The aim of this study is to determine the diagnostic value of high-resolution 3D unenhanced ECG-gated respiratory-navigated MR angiography (MRA) of the renal arteries using a steady-state free precession (SSFP) technique in comparison with 1.0-molar contrast-enhanced MRA in patients with suspected renal artery stenosis. - - SUBJECTS AND METHODS. Forty-five consecutive patients underwent unenhanced MRA before contrast-enhanced MRA within the same session. We assessed examination time, image quality, renal artery architecture, and localization and severity of renal artery stenosis. - - RESULTS. Examination time was shorter for contrast-enhanced MRA (mean ± SD, 12 ± 3 minutes) than for unenhanced MRA (19 ± 3 minutes; p < 0.001). On a 5-point scale, the image quality was similar for contrast-enhanced MRA (3.8 ± 1.0) and unenhanced MRA (4.0 ± 1.3; p = 0.24). Contrast-enhanced MRA offered more assessable data sets than did unenhanced MRA (95% vs 90%); however, unenhanced MRA had more data sets with maximum image quality (49% vs 30%). There was moderate agreement in stenosis grading between both MRA techniques (κ = 0.51; p < 0.001), but in only one case (1.3%) we found mismatch of more than one severity stenosis grade (stenoses > 75%). Sensitivity, specificity, and positive and negative predictive values of unenhanced MRA to detect renal artery stenoses greater than 50% were 75%, 99%, 75%, and 99%, respectively. - - CONCLUSION. We show that SSFP 3D unenhanced MRA is a very promising technique for patients with suspected renovascular disease and could be used as an alternative if gadolinium-based contrast agents cannot be administered.
Gesehen am 28.04.2023